Associação entre genes HLA e KIR e sensibilização a ácaros em uma população brasileira - Caniatti, Marcela Caleffi da Costa Lima (2016)
Sensitization to dust mites affects between 15 to 20% of the population in industrialized countries and is influenced by several genetic and environmental factors. Allergic reactions are triggered by allergens in certain pre-sensitized individuals who have specific IgE antibodies on the surface of the mast cells, causing the release of vasoactive substances. Immune response genes are one of the candidates responsible for the susceptibility of atopic diseases. The interactions of the KIR (killer cell immunoglobulin-like receptors) isotypes, present in NK (natural killer) cells, with certain HLA (human leukocyte antigen) class I molecules are known to maintain homeostasis. HLA molecules are responsible for the presentation of peptides to the T lymphocytes and the KIR receptors controls the activation/inhibition of NK cells, functions that could explain the associations observed with certain allergies. Conduct a genetic association study, to investigate markers of immune response in Class I (-A, -B, and -C) and Class II (-DRB1) HLA genes, and KIR genes in mite-sensitive individuals (D. farinae, D. pteronyssinus, or Blomia tropicalis) and controls. A total of 396 participants were classified as mite-sensitive and mite-insensitive individuals, after the immediate-type hypersensitivity skin test - Prick Test . Genotyping of HLA (human leukocyte antigen) genes and the presence/absence of KIR genes were performed by PCR-SSO (polymerase chain reaction-sequence specific oligonucleotides). After the heterogeneity test, the HLA-DRB1 locus presented a significant difference between the frequencies of the sensitive and non-sensitive individuals for the DRB1*04:11 allele (1.2% vs. 4.4%, P = 0.0042, OR = 0.26 and 95% IC = 0.09-0.70). For KIR receptors and their respective ligands, no significant difference was observed. Our results suggest a possible association between HLA-DRB1 genes and dust mite sensitization.